Combined Effects of Obstructive Sleep Apnea and Sleep Duration on Hypertension in Korean Adults: A Nationwide Study - Seo Young Kang; Yunmi Kim (Biomedicines)
Background: Obstructive sleep apnea (OSA) and abnormal sleep duration are known risk factors for hypertension. However, evidence regarding their combined effect on hypertension is limited and inconsistent. This study aimed to examine the independent and interactive associations of OSA risk and sleep duration with hypertension in Korean adults. Methods: We analyzed data from 14,579 adults aged ≥40 years who participated in the 2019–2022 Korea National Health and Nutrition Examination Survey. OSA risk was assessed using the STOP-Bang questionnaire and classified as low (0–2), moderate (3–4), or high (5–8). Sleep duration was self-reported and categorized as <6, 6–<7, 7–<8, 8–<9, and ≥9 h. Hypertension was defined based on measured blood pressure and antihypertensive medication use. Multivariate logistic regression was conducted to evaluate the associations. Results: A dose–response association was observed between OSA risk and hypertension prevalence: adjusted ORs (95 CIs) were 9.69 (8.37–11.23) for moderate and 36.58 (29.35–45.59) for high OSA risk. Sleep duration alone was not significantly associated with hypertension. However, interaction models showed a U-shaped relationship, with the lowest hypertension prevalence in those sleeping 7–<8 h. Among participants with high OSA risk, both short (<7 h) and long (≥9 h) sleep durations were associated with significantly higher hypertension risk (OR 48.49, 95% CI 19.68–119.50 for ≥9 h). Conclusions: OSA risk and sleep duration jointly affect hypertension risk. Individuals with high OSA risk who are short or long sleepers may require targeted interventions to improve blood pressure control.